Granular Cell Tumors (KYAMC Journal, 2023)
GCTs (Granular Cell Tumors) are rare, uncommon STTs (Soft Tissue tumors) that may develop at any location in the human body. Though the initial one was identified first as a non-capsulated granular cell myoblastoma of the tongue, they are now identified immunohistochemically as principally of neural Schwann cell origin (S-100 marker positive). Still more rarely, non-neural GCTs are also described that are probably of mesenchymal origin (as evidenced by S-100 marker negativity and vimentin positivity). Though they are more common in females and black people in the third to sixth decades of life, no sex, no race, and no age group are immune to this disease. They are mostly benign and very rarely malignant. Exact history taking, physical examination and laboratory investigations, including histopathological, histochemical, and immunohistochemical examinations, are essential to arrive at a concrete diagnosis, as many other tumors (e.g., malignant melanoma, small cell lung cancer, etc.) in the body resemble GCTs both histologically (granularity) and by biological behavior (benign, malignancy, recurrency at primary and metastatic sites). Benign variants have clinical features depending on location and are universally cured by wide surgical excision. The malignant variant carries a worse prognosis. These rare GCTs are to be kept in mind always in the differential diagnosis of soft tissue swellings anywhere in the body. Their biological and pathological features, differential diagnosis, and therapeutic implications are discussed here, briefly reviewing the available literature.KYAMC Journal Vol. 14, No. 02, July 2023: 96-101.